Investigation on the thermo-electric-electrochemical characteristics of retired LFP batteries for echelon applications. Issue 22 (11th May 2022) - Lv, Youfu; Luo, Weiming; Mo, Ya; Zhang, Guoqing
Abstract : Electric vehicles (EVs) have been developed to alleviate environmental pollution and climate change, but they leave behind a large amount of retired lithium-ion batteries (LIBs). Abstract : Electric vehicles (EVs) have been developed to alleviate environmental pollution and climate change, but they leave behind a large amount of retired lithium-ion batteries (LIBs). Since the replacement of LIBs from EVs will lead to considerable waste generation, improving the echelon utilization of retired LIBs is becoming increasingly critical. In this paper, we studied the thermo-electric-electrochemical performance of retired LiFePO4 (LFP) batteries using traditional methods, and found that the remaining capacity of retired LFP batteries has a strong correlation with their internal resistance. This result helped us to propose a rapid and elementary classification method for the calibration of the remaining capacity, and to then formulate a test protocol seeking to balance the time spent and the test cost. Besides, the cut-off voltage and charge–discharge current density have a significant impact on the calibration of the remaining capacity, especially for retired LFP batteries with low residual capacity. In the cycle life test and temperature reliability evaluation process, the results demonstrate that the retired LFP batteries have a good service life when under a lower current of charge/discharge, and the capacity reductions were 2.3%, 11.2% and 4.8% for retired LFP batteries with 80% state of health (SOH), 70% SOH and 60% SOH, respectively, after 500 cycles. Finally, considering the temperature reliability, voltage consistency and large current cycling performance of retired LFP batteries, there are still many challenges in their future echelon utilization.